Punicalagin as a novel tyrosinase and melanin inhibitor: Inhibitory activity and mechanism. (1st May 2022) - Yu, Zi-Yi; Xu, Ke; Wang, Xuan; Wen, Yi-Ting; Wang, Lin-Jun; Huang, De-Qiang; Chen, Xiao-Xin; Chai, Wei-Ming
Abstract: The inhibition of punicalagin on tyrosinase and melanogenesis was investigated through multiple spectroscopic approaches, molecular docking, molecular dynamic simulation, cell assay, and preservation assays. The results confirmed that punicalagin significantly inhibited tyrosinase activity in vitro (IC50  = 0.64 ± 0.05 mM) and B16F10 cells (IC50  = 16 ± 0.7 μM). The binding of punicalagin to tyrosinase changed the conformation of the enzyme by influencing the hydrophobicity and polar environment of the binding site. The results of molecular docking and thermodynamic analysis showed that hydrophobic interaction and hydrogen bond were major driving forces in stabilizing the punicalagin-tyrosinase complex, influencing substrate-binding affinity to tyrosinase and resulting in tyrosinase activity reduction. Molecular dynamic analysis indicated that punicalagin stretched the basic framework structure of tyrosinase and lowered the surface hydrophobicity of the enzyme. Cell analyses further demonstrated that punicalagin inhibited melanogenesis by down-regulating the expressions of MITF and tyrosinase. What's more, preservation assays showed that punicalagin could reducing the oxidation of phenols to melanin by inhibiting the polyphenol oxidase, thereby preventing the browning of fresh-cut apples. These findings provided new perspectives on the inhibition mechanism of punicalagin on tyrosinase/melanogenesis and a theoretical support for its feasible application in the food and medicine industry. Highlights: Punicalagin displayed effective anti-tyrosinase activity in vitro and cells. Punicalagin change the conformation of enzyme by reducing hydrophobicity and stretching the backbone. Punicalagin reduce melanin by down-regulating the MITF and tyrosinase proteins. Punicalagin delay browning by lowering PPO activity and reducing phenolic oxidation.